2014
DOI: 10.1016/j.jaci.2014.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Basophils regulate the recruitment of eosinophils in a murine model of irritant contact dermatitis

Abstract: Eosinophils mediated the development of murine ICD, possibly through ROS production. Recruitment of eosinophils into the skin was induced by basophils in cooperation with fibroblasts. Our findings introduce the novel concept that basophils promote the recruitment of eosinophils into the skin through fibroblasts in the development of skin inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 45 publications
(47 reference statements)
2
59
0
4
Order By: Relevance
“…Cross-linking of high affinity receptors with antigen-specific IgE complexes leads rapidly to degranulation and secretion of inflammatory mediators such as histamine, leukotrienes, cytokines and chemokines, which are important in the development of acute and chronic allergic responses [11,12]. In addition, a recent study suggests that basophils are able to infiltrate rapidly into the http inflamed skin and subsequently recruit eosinophils for the development of inflammatory lesions in murine models [13]. In that study, recruitment of eosinophils was induced by production of IL-4 and TNF-a from basophils in contact with fibroblasts, promoting the expression of eotaxin and RANTES from the fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-linking of high affinity receptors with antigen-specific IgE complexes leads rapidly to degranulation and secretion of inflammatory mediators such as histamine, leukotrienes, cytokines and chemokines, which are important in the development of acute and chronic allergic responses [11,12]. In addition, a recent study suggests that basophils are able to infiltrate rapidly into the http inflamed skin and subsequently recruit eosinophils for the development of inflammatory lesions in murine models [13]. In that study, recruitment of eosinophils was induced by production of IL-4 and TNF-a from basophils in contact with fibroblasts, promoting the expression of eotaxin and RANTES from the fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have revealed that basophils and mast cells play distinct roles in immune responses such as allergic inflammation and protective immunity to parasitic infections (2)(3)(4). Basophils also contribute to immune regulation through their interaction with other types of cells, including T cells (5)(6)(7)(8), monocytes (9,10), innate lymphoid cells (11), fibroblasts (12,13), and endothelial cells (14).…”
mentioning
confidence: 99%
“…39 Co-cultivation with fibroblasts increased basophil CCL5 expression, while basophils induced elevated eotaxin/CCL11 expression in the fibroblasts. 39 In our results, a large number of dermal fibroblasts and a dramatic infiltration of basophils and eosinophils were observed in the AD-like skin lesions (Figure 3). Because they are accessible to each other in vivo, we hypothesized that basophils and eosinophils might be activated in synergy with dermal fibroblasts in response to NOD2/TLR2 ligands.…”
Section: Discussionmentioning
confidence: 93%